2022
DOI: 10.1155/2022/9665421
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Coordination Graph Convolution Reinforcement Learning for Multi-Intelligent Vehicle Driving Policy

Abstract: With the growing up of Internet of Things technology, the application of Internet of Things has been popularized in the field of intelligent vehicles. Therefore, more artificial intelligence algorithms, especially DRL methods, are more widely used in autonomous driving. A large number of deep reinforcement learning (RL) technologies are continuously applied to the behavior planning module of single-vehicle autonomous driving in early. However, autonomous driving is an environment where multi-intelligent vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Similarly, Zhang et al (2021) [63] extended the Unified Theory of Technology Acceptance and Use model and found that risk expectation and consumer innovativeness are influential factors in the acceptance of autonomous vehicles. The development of autonomous vehicles has been facilitated by advances in artificial intelligence (AI) and machine learning (ML) technologies [66][67][68]. The cybersecurity of autonomous vehicles has also been a matter of debate.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%
“…Similarly, Zhang et al (2021) [63] extended the Unified Theory of Technology Acceptance and Use model and found that risk expectation and consumer innovativeness are influential factors in the acceptance of autonomous vehicles. The development of autonomous vehicles has been facilitated by advances in artificial intelligence (AI) and machine learning (ML) technologies [66][67][68]. The cybersecurity of autonomous vehicles has also been a matter of debate.…”
Section: Literature Review Research Model and Hypothesesmentioning
confidence: 99%